Reinvestigating the effect of trade openness towards government size, government expenditure and exchange rate: evidence from Malaysia / Nurul Syafika Abdul Malik and Rosaieni Saiful Arulchelvan - Abdul Malik, Nurul Syafika; Saiful Arulchelvan, Rosaieni (2013)
This paper investigates the short run and long run relationship between the effect of trade openness towards government size, government expenditure and exchange rate in Malaysia. Data for the variables were obtained from World Development Indicators (WDI) from 1988 to 2010. Based on our analyses, we had come out we two model that is trade openness(TO) = - government size(GS)+ exchange rate(ER) and the other model is trade openness(TO) = government expenditure(GDP)=exchange rate(ER).However the study discovers that second model have long run relationship instead of first model. Other than that, we identify that government expenditure is variable that cause trade openness and exchange rate. A few policies implication can be recommended such as government may increase trading activity such as import and export activity. Beside that the government right now needs to implement the economic transforming program more effectively. We also recommend that Malaysia should involve in more trade agreement beside FTA and WTO. The trade agreement that Malaysia can involve is maybe European Union that promise more opportunity to do the trade. In order to make sure this program success Malaysia government have to get cooperation from the private sector and not rely on the policy that implement by the government only.